Dry and neovascular “wet” age-related macular degeneration: Upcoming therapies - Audrey Yan; Nasiq Hasan; Jay Chhablani (Indian Journal of Ophthalmology)
The age-related macular degeneration (AMD) field is witnessing promising advancements in therapeutic options. Breakthrough drugs such as pegcetacoplan and avacincaptad have been FDA-approved for dry AMD, marking a significant development as there were no treatment options until August 2023. While several antivascular endothelial growth factor (VEGF) inhibitors have been approved for wet AMD, challenges persist with the need for frequent dosing. New treatments such as gene therapy, cell therapy, WNT pathway agonists, complement inhibitors, and anti-VEGF combination drugs are under development to address these issues. These developments are exciting and hold promise for transforming the field of medicine, offering hope for improved outcomes and enhanced patient care in managing AMD.